Kajian Tarif Air Untuk Beberapa Negeri Di Utara Semenanjung Malaysia - Abdullah, Noor Hazalina (Universiti Sains Malaysia, 2006)
Water is the most important basis necessity. Before the raw water can be distributed to the consumer, it has to be processed to maintain its purity and cleanliness. For this particular reason, the authority should charge the consumer to pay for the cost involved. The main objective of this study is to know the rational taken by the authorities to increase the water tariff for certain states in Malaysia especially for the states which are located at north of Peninsular Malaysia such as Kedah, Perak and Pulau Pinang. Data collection for this study was taken from the authorities that are involved directly in the water distribution sector. From this study, it indicates that the increase of tariffs is due to several factors that can be considered fair and reasonable for both domestic and industrial users. This study also provide the comprehension about the reasons and rationales that has been taken for increasing water tariff in certain states in Malaysia which can be used for any further study.